2023
DOI: 10.3389/fonc.2023.1171699
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology for health shows disparities in cancer prevention between digital health technology users and the general population in Romania

Bogdan C. Pana,
Nicolae Ciufu,
Carmen Ciufu
et al.

Abstract: IntroductionDigital health services and technology are rapidly developing following the COVID-19 pandemic. This study aimed to reveal the differences between users of digital health technology (DHT) and the general population with regard to cancer prevention.Materials and MethodsThis was an observational study on a conventional sample of 270 DHT users with completed data, performed in September 2021.ResultsA significant difference was observed in the proportion of DHT users and the general population reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Regular exercise is also essential for maintaining physical function and vitality [ 4 , 5 ]. A healthy and balanced diet plays a crucial role in supporting the immune system and improving the energy of cancer patients, even when combined with specific supplements inspired by nature.…”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise is also essential for maintaining physical function and vitality [ 4 , 5 ]. A healthy and balanced diet plays a crucial role in supporting the immune system and improving the energy of cancer patients, even when combined with specific supplements inspired by nature.…”
Section: Introductionmentioning
confidence: 99%
“…Screening and early detection are among the primary priorities of the current European anticancer plan and should be implemented at the national level ( Pana et al, 2023 ). Within our Research Topic, three original research articles emphasized the significance of on national level screening.…”
mentioning
confidence: 99%
“…Their findings revealed that inducing TGF-β1 resulted in a significant increase in autophagosome formation and autophagic flux in different molecular cascades. Another original research studied by Jia et al demonstrated the in vivo efficacy of hesperidin in promoting gastric motility in rats with functional dyspepsia, suggesting a potential treatment approach for this condition.Screening and early detection are among the primary priorities of the current European anticancer plan and should be implemented at the national level (Pana et al, 2023). Within our Research Topic, three original research articles emphasized the significance of on national level screening.…”
mentioning
confidence: 99%